Three Main Directions Of Modern Higher Medical Education (Eurasian Journal of Learning and Academic Teaching, 2024)
The authors propose the main directions for training competitive professionals who have the competencies to meet the needs of a changing labor market, capable of developing the scientific and technical potential and socio-economic development of the country, and continuing active integration into the world community. The fundamental task on the track of higher medical education in modern realities is to obtain an education that includes a combination of three functions: mastering academic culture, learning a profession and training new scientists. These brief formulations contain the essence of a single educational, educational and pedagogical process of a modern higher medical school